The Effect of Fasting on Erectile Function and Sexual Desire on Men in the Month of Ramadan - Talib, Raidh A.; Canguven, Onder; Al-Rumaihi, Khalid; Al Ansari, Abdulla; Alani, Mohammed (Urology Journal, 2015)
Purpose: To determine the effect of Ramadan intermittent fasting on erectile function (EF), sexual desire and serum hormone levels. Materials and Methods: Eligible male participants completed the two domains of International Index of Erectile Function (IIEF) questionnaire for EF and sexual desire. They also provided information on any known disease, treatment taking, smoking habits and frequency of sexual intercourse. Frequency of sexual intercourse, two domains of IIEF questionnaire, serum hormone levels, body weight before and four-weeks after the end of month of Ramadan were also recorded. Results: Overall, 45 men, with a mean age of 37 ± 7.2 years, participated in the study. Frequency of sexual intercourse (P = .046), sexual desire (P = .002), body weight (P = .009) and serum follicle stimulating hormone (FSH) level (P = .016) decreased significantly at the end of month of Ramadan compared to baseline. No statistically significant differences were found on EF (P = .714), serum testosterone (P = .847), luteinizing hormone (P = .876), estradiol (P = .098) and dehydroepiandrosterone sulfate levels (P = .290). Conclusion: Ramadan intermittent fasting might be associated with decrease in sexual desire, frequency of sexual intercourse and serum FSH level.